A Review and Comparative Analysis of Digital Literacy Frameworks – Where Are We Heading and Why? - LEE, Yoo -Taek; FANEA-IVANOVICI, Mina (Theoretical and Practical Research in Economic Fields; Vol 14 No 2 (2023): TPREF, Volume XIV, Issue 2(28), Winter 2023, 2023)
Digital literacy has become as important as other types of literacies that schools and universities teach. In this context, defining it and understanding its components are critical in order to be able to design meaningful policies meant to improve the digital literacy level of the population and to create adequate and well-articulated educational tools and curricula. The purpose of this paper is to identify, briefly describe and compare the existing digital literacy frameworks issued by academia, as well as by governmental and international organizations. Based on this comparative analysis, the paper concludes as to the strengths of the most recent and comprehensive digital literacy framework and discusses the need of progression from earlier frameworks to the most recent ones.